Effects of dexamethasone, cyproheptadine, anisodamine, and dinoprostone on TNF alpha production in endotoxic shock - Wang Li-zan; Liu Yu-qin; Cui Yun-he; Zhu Fan-he; Wang Bao-sheng; Lun Ning (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of dexamethasone (Dex), cyproheptadine (Cyp), anisodamine (Ani), and dinoprostone (Din) on lipopolysaccharides (LPS)-induced tumor necrosis factor alpha (TNF alpha) gene expression and antishock effects of inhibiting TNF alpha production. METHODS: Endotoxic shock in rats was produced by i.v. injection of LPS (E coli O111B4, 5 mg.kg-1). TNF alpha mRNA accumulation was assessed by Northern blot. Plasma TNF alpha contents were determined by radioimmunoassay. RESULTS: The TNF alpha mRNA levels in rat liver at 2 h after LPS challenge was increased obviously (autoradiograms analyzed by scanning were 38 +/- 10 vs saline control 11 +/- 8, P < 0.01). The plasma TNF alpha contents were markedly increased [(22 +/- 3) micrograms.L-1 vs saline control (2.2 +/- 1.0) micrograms.L-1, P < 0.01]. Dex 5, Cyp 5, Ani 10, or Din 2 mg.kg-1 immediately injected after i.v. LPS markedly decreased the TNF alpha mRNA levels in rat liver and plasma TNF alpha contents. The Dex, Cyp, Ani, and Din improved the mouse survival rate 24 h after LPS 20 mg.kg-1 challenge. CONCLUSION: Dex, Cyp, Ani, and Din strongly inhibit LPS-induced TNF alpha gene expression, and have a beneficial antishock effects.